Tinctorial behavior of curaua and banana fibers and dyeing wastewater treatment by porous alumina membranes. Issue 6 (1st February 2016) - Oliveira, Fernando R.; Galvão, Felipe M.F.; da Silva, Tábhita L.T.; Silva, Késia Karina O.S.; Nascimento, José H.O.; Souto, António P.; Zille, Andrea
Abstract: Physicochemical and dyeing properties using reactive dyes of curaua and banana fibers were studied by means of color strength ( K / S ), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), and Fourier transform infrared (FTIR) spectroscopy analyses. SEM analysis of alkali-treated fibers showed an increase in roughness due to surface lignin and hemicellulose defibrillation. DSC analysis showed for all the samples an endothermic and an exothermic peak at 70–80 and 340–360°C due to the loss of adsorbed/absorbed water and to decomposition of α-cellulose, respectively. Alkali-treated fibers displayed a second peak around 290°C attributed to the degradation of hemicellulose. FTIR spectra of the studied fibers show similar bands with different intensities attributed to the main components of cellulose-based materials. Alkali-pretreated fibers demonstrated excellent dyeing ability for all the tested dyes. Dye absorption depends on the chemical fiber, dye structure, and concentration. The results of washing fastness are very good for all the tested fibers. The dyeing effluent treated with an advanced microfiltration method using an improved alumina ceramic membrane shows an average efficiency of 98% in turbidity and color reduction. Low-cost ceramic alumina microfiltration membranes are a very promising advanced treatment for textile industrial effluents allowing water reuse.